(untitled) (American Journal of Islam and Society, 1985)
"Whence did you enslave people who were born free?" (Umar Ibn-al-Khattab) The growth of public administration and the increasing influence of administrative agencies on public policy make the perennial political problem of the control of administration more important than ever. Governmental activities nowadays touch so many people, in so many ways, that citizens’ dissatisfaction with administration is inevitable. Many countries have sought protections and safeguards against oppressive, mistaken, or careless exercise of public authority. Although the bureaucrats act as a leveling and rationalizing force, they are susceptible to certain persistent maladies. W.A. Robson has identified these as excessive sense of self-importance; indifference to the feelings or convenience of others, obsessive to established practice regardless of resulting hardships, persistent addiction to formality, and astigmatic inability to perceive the totality of the government because of preoccupation with one of its parts. When these maladies exist, they may not be instantly recognized and treated, because administrative work often occurs beyond the gaze of professional observers. Moreover, many of the individuals with whom administrators deal offensively are likely to be anonymous and the injustices invisible. The purpose of this study is to show that Islam had developed prominent external critics of administration long before the major countries had developed their current protective mechanisms against bureaucratic excesses. The main objective is to integrate the major Islamic critics of administration found in lslamic literature .and their current equivalent in modern countdea so that they become more compatible with the contextual timing and demands of daily administrative life. A comparative approach will facilitate the ...